PELATIHAN PENGHITUNGAN HPP (METODE PERIODIK) PERUSAHAAN DAGANG DAN MANUFAKTUR PADA SISWA SMAN 20 KABUPATEN TANGERANG - Herni Kurniawati; Tania Liliana Troi; Alanis Kezia Tatengkeng (PROSIDING SERINA, 2021)
PKM has a goal to help students of SMA Negeri 20 Tangerang Regency to understand the science of accounting in depth, especially the company's cost of goods sold the periodic method and what items make up the cost of goods sold. PKM uses qualitative data, namely primary data in the form of interviews with principals and teachers, so this PKM is categorized as descriptive qualitative research. In addition, the data is information in the form of evidence of financial transactions for one period. Other data needed during PKM is secondary data in the form of books, journals, internet sources that support this PKM. The result of the PKM is that it has been well implemented on Thursday 11 November 2021 with enthusiasm from the students of SMAN 20 Tangerang Regency. The output from the results of this Community Service is the proceedings of the national seminar as a presenter and also articles that are uploaded to PINTAR as additional outputs.